Karakter Morfologi Dan Hubungan Kekerabatan Pada Tanaman Jahe (Zingiber officinale) di Kabupaten Garut: Morphological Character and Relationships of Ginger (Zingiber officinale) Plants in Garut Regency - Lestari, Indri; Hakiki, Nisa; Nurjanah, Sindi; Jamil, Tedi Kustiadi; Sativa, Novriza (Departemen Biologi, Institut Pertanian Bogor, 2024)
Ginger (Zingiber officinale) is one of the spice plants used for cooking or traditional medicine in Indonesia. Ginger variations are highly diverse in the Garut region, hence there is a need for the characterization of ginger plants to identify the germplasm present in the Garut area. This research was conducted at several points in the Garut region by observing the morphological characteristics of ginger based on Union for the Protection of New Varieties of Plants. The morphological characteristics observed include overall plant morphology, including stem, leaves, and rhizomes. After the data were collected based on predetermined criteria according to descriptors, the data were processed using NTSYS 2.1 to determine the relatedness of the ginger varieties found. Based on the analysis of the dendrogram results, it is shown that among the red ginger varieties (A1 and A5), there is a coefficient value of 0.65, indicating a high similarity in properties. Elephant ginger (A3, A2) and emprit ginger (A6) have a coefficient value of 0.45, indicating a close relatedness between elephant ginger and red ginger, while elephant ginger (A4 and A7) has a coefficient value of 0.50, indicating close relatedness.